Synthesis and fabrication of gelatin-based elastomeric hydrogels through cosolvent-induced polymer restructuring. Issue 13 (10th March 2022) - Panwar, Amit; Sk, Md Moniruzzaman; Lee, Bae Hoon; Tan, Lay Poh
Abstract : Hydrogels have a wide range of applications in tissue engineering, drug delivery, device fabrication for biological studies and stretchable electronics. Abstract : Hydrogels have a wide range of applications in tissue engineering, drug delivery, device fabrication for biological studies and stretchable electronics. For biomedical applications, natural polymeric hydrogels have general advantages such as biodegradability and non-toxic by products as well as biocompatibility. However, applications of nature derived hydrogels have been severely limited by their poor mechanical properties. For example, most of the protein derived hydrogels do not exhibit high stretchability like methacrylated gelatin hydrogel has ∼11% failure strain when stretched. Moreover, protein derived elastomeric hydrogels that are fabricated from low molecular weight synthetic peptides require a laborious process of synthesis and purification. Biopolymers like gelatin, produced in bulk for pharma and the food industry can provide an alternative for the development of elastomeric hydrogels. Here, we report the synthesis of ureidopyrimidinone (Upy) functionalized gelatin and its fabrication into soft elastomeric hydrogels through supramolecular interactions that could exhibit high failure strain (318.73 ± 44.35%). The hydrogels were fabricated through a novel method involving co-solvent optimization and structural transformation with 70% water content. It is anticipated that the hydrogel fabrication method involves the formation of hydrophobic cores of ureidopyrimidinone groups inside the hydrogel which introduced elastomeric properties to the resulting hydrogel.